A profile of resuscitations at the Kalafong hospital emergency unit - L. Engelbrecht; S. Smith; M. Geyser (South African Family Practice)
Background: All serious emergency cases arriving at the Kalafong Hospital emergency department are first resuscitated by doctors from the Family Medicine Department. The aim of this study was to construct a profile of the patients that the emergency unit doctors consider necessary to admit to the resuscitation unit and to describe the procedures carried out on them.